The «Areola» system database - Bryzgalov, P.A. (Numerical Methods and Programming (Vychislitel'nye Metody i Programmirovanie), 2005)
The paper describes the database of the «Areola» system mdash; a program shell for creating online encyclopedia. In particular, the database structure, the processes of initial data input, detecting errors and editing information in the database are described.